2014
DOI: 10.1016/j.ajog.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin 1 and 2 serum concentrations in first trimester of pregnancy as biomarkers of adverse pregnancy outcomes

Abstract: Word count:Abstract: 250 Text: 3,183 2 Condensation: Ang-2 and the Ang-1/Ang2 ratio is associated with several adverse pregnancy outcomes but do not predict complications any better than maternal risk factors Short title: Ang-1 and Ang-2 as biomarkers of adverse pregnancy outcomes 3 ABSTRACTObjective: To assess Ang-1, Ang-2 and the Ang-1/Ang-2 ratio levels in the first trimester of pregnancy, their association with adverse pregnancy outcomes; and their predictive accuracy.Study Design: This cohort study measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Subsequently, others authors confirmed the presence of an anti-angiogenic state in preeclampsia as well as in other pregnancy-related disorders [15,16]. Indeed, there is a growing body of evidence that anti-angiogenic mediators in maternal serum may serve as potential biomarkers for adverse pregnancy outcomes [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, others authors confirmed the presence of an anti-angiogenic state in preeclampsia as well as in other pregnancy-related disorders [15,16]. Indeed, there is a growing body of evidence that anti-angiogenic mediators in maternal serum may serve as potential biomarkers for adverse pregnancy outcomes [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…These associations may suggest the role of angiogenic/anti-angiogenic factors in the pathogenesis of adverse pregnancy outcomes, however, their value in screening of women at-risk of these conditions may be not appropriate in a clinical setting. In a recent study, we found that despite a positive association between elevated first trimester Ang-1/Ang-2 ratio levels with SGA, preeclampsia, preterm birth and miscarriage in a large cohort of women 9 , the overall predictive accuracy was poor. Strengths of the study were the evaluation of a large sample from a population-based cohort of pregnant women attending first trimester screening.…”
Section: Discussionmentioning
confidence: 99%
“…Ang-1 and Ang-2 concentrations were available for 1,058 women and were obtained from data from a previous study 9 . 21 and categorized into quintiles.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers and biophysical tests may improve the accuracy of the model beyond using maternal characteristics alone. Published studies show only a limited contribution of these factors to improved discriminative performance, however . Moreover, most of these more complex predictors are relatively expensive, not readily available in general antenatal settings, and are possibly inconvenient for pregnant women .…”
Section: Introductionmentioning
confidence: 99%